2018
DOI: 10.1111/cei.13213
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic Plasmodium infection during pregnancy is associated with reduced antibody levels to tetanus toxoid

Abstract: Submicroscopic Plasmodium infections in pregnancy are common in endemic areas, and it is important to understand the impact of these low-level infections. Asymptomatic, chronic infections are advantageous for parasite persistence, particularly in areas where the optimal eco-epidemiological conditions for parasite transmission fluctuate. In chronic infections, the persistence of the antigenic stimulus changes the expression of immune mediators and promotes constant immune regulation, including increases in regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…However, it is important to note that each study includes different groups and different clinical presentation of malaria. In a recent study carried out in pregnant women, submicroscopic infection by Plasmodium was associated with a decrease in the levels of IgG against tetanus toxoid [37]. In the same way, of four studies that evaluated the effect of filarioidosis in the immune response against tetanus toxoid, two showed a decrease in IgG levels against tetanus toxoid vaccine [38,39], while two did not show differences between the groups [33,40] (Table 1).…”
Section: Discussionmentioning
confidence: 81%
“…However, it is important to note that each study includes different groups and different clinical presentation of malaria. In a recent study carried out in pregnant women, submicroscopic infection by Plasmodium was associated with a decrease in the levels of IgG against tetanus toxoid [37]. In the same way, of four studies that evaluated the effect of filarioidosis in the immune response against tetanus toxoid, two showed a decrease in IgG levels against tetanus toxoid vaccine [38,39], while two did not show differences between the groups [33,40] (Table 1).…”
Section: Discussionmentioning
confidence: 81%
“…An important achievement of this study was to describe the histological alterations that are frequent in placentas with submicroscopic infections. There are reports that do not show associations between submicroscopic infections and negative pregnancy outcomes [10,32,[54][55][56], but there are also reports that submicroscopic infection during pregnancy affects the health of the mother and the fetus [10-12, 32, 55, 57-59]. These infections in maternal peripheral blood or in the placenta may cause pathological effects on maternal and infant health, although, apparently, with lesser magnitude than microscopic infections.…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, an area of low transmission of both P. falciparum and P. vivax, there is a high frequency of submicroscopic gestational and placental infections, 49% and 57%, respectively [11]. The impact of submicroscopic infections of both species in pregnancy in this area is being explored, and it has been shown that submicroscopic infection during pregnancy is frequent and can affect the health of women and their offspring [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…41 Most of the studies on the immune response in MAP focus mainly on P. falciparum infections, they agree that the consequences of MAP go beyond infection during pregnancy, since its effects extend to the neonate and the first years of life. 25 In pregnancy is not known how antiplasmodial antibodies (Ab) maintain protective levels, and its levels in reinfections are not known either. Despite this absence, a study in northwestern Thailand measured Ab levels against merozoite antigens (m-Ag) from both species and against VAR2CSA antigens from P. falciparum.…”
Section: Immunity In Mapmentioning
confidence: 99%
“…Something similar occurs with the prevalence of PM and CM, demonstrating that submicroscopic infections (detected with PCR, but not with TBS) affect maternal health, the placenta and affect the gestational product. 23,25,26 Coexistence of GM and PM GM is prior to infection of the placenta (PM). The first can exist without the second and PM can be without GM, but the usual is their coexistence.…”
Section: Frequency Mapmentioning
confidence: 99%